Trajectories of childhood neighbourhood cohesion and adolescent mental health: evidence from a national Canadian cohort. Issue 15 (14th July 2015) - Kingsbury, M.; Kirkbride, J. B.; McMartin, S. E.; Wickham, M. E.; Weeks, M.; Colman, I.
Abstract : Background: The objective of this study was to examine associations between trajectories of childhood neighbourhood social cohesion and adolescent mental health and behaviour. Method: This study used data from the National Longitudinal Survey of Children and Youth, a nationally representative sample of Canadian children. The sample included 5577 children aged 0–3 years in 1994–1995, prospectively followed until age 12–15 years. Parental perceived neighbourhood cohesion was assessed every 2 years. Latent growth class modelling was used to identify trajectories of neighbourhood cohesion. Mental health and behavioural outcomes were self-reported at age 12–15 years. Logistic regression was used to examine associations between neighbourhood cohesion trajectories and outcomes, adjusting for potential confounders. Results: Five distinct trajectories were identified: 'stable low' (4.2%); 'moderate increasing' (9.1%); 'stable moderate' (68.5%); 'high falling' (8.9%); and 'stable high' (9.3%). Relative to those living in stable moderately cohesive neighbourhoods, those in stable low cohesive neighbourhoods were more likely to experience symptoms of anxiety/depression [odds ratio (OR) = 1.73, 95% confidence interval (CI) 1.04–2.90] and engage in indirect aggression (OR = 1.62, 95% CI 1.07–2.45). Those with improvements in neighbourhood cohesion had significantly lower odds of hyperactivity (OR = 0.67, 95% CI 0.46–0.98) and indirect aggression (OR = 0.69, 95% CI 0.49–0.96). In contrast, those with a decline in neighbourhood cohesion had increased odds of hyperactivity (OR = 1.67, 95% CI 1.21–2.29). Those in highly cohesive neighbourhoods in early childhood were more likely to engage in prosocial behaviour ('high falling': OR = 1.93, 95% CI 1.38–2.69; 'stable high': OR = 1.89, 95% CI 1.35–2.63). Conclusions: These results suggest that neighbourhood cohesion in childhood may have time-sensitive effects on several domains of adolescent mental health and behaviour.